In vitro inhibitory effects of plant-based foods and their combinations on intestinal α-glucosidase and pancreatic α-amylase - Adisakwattana, Sirichai (BioMed Central, 2012)
BACKGROUND: Plant-based foods have been used in traditional health systems to treat diabetes mellitus. The successful prevention of the onset of diabetes consists in controlling postprandial hyperglycemia by the inhibition of α-glucosidase and pancreatic α-amylase activities, resulting in aggressive delay of carbohydrate digestion to absorbable monosaccharide. In this study, five plant-based foods were investigated for intestinal α-glucosidase and pancreatic α-amylase. The combined inhibitory effects of plant-based foods were also evaluated. Preliminary phytochemical analysis of plant-based foods was performed in order to determine the total phenolic and flavonoid content. METHODS: The dried plants of Hibiscus sabdariffa (Roselle), Chrysanthemum indicum (chrysanthemum), Morus alba (mulberry), Aegle marmelos (bael), and Clitoria ternatea (butterfly pea) were extracted with distilled water and dried using spray drying process. The dried extracts were determined for the total phenolic and flavonoid content by using Folin-Ciocateu’s reagent and AlCl(3) assay, respectively. The dried extract of plant-based food was further quantified with respect to intestinal α-glucosidase (maltase and sucrase) inhibition and pancreatic α-amylase inhibition by glucose oxidase method and dinitrosalicylic (DNS) reagent, respectively. RESULTS: The phytochemical analysis revealed that the total phenolic content of the dried extracts were in the range of 230.3-460.0 mg gallic acid equivalent/g dried extract. The dried extracts contained flavonoid in the range of 50.3-114.8 mg quercetin equivalent/g dried extract. It was noted that the IC(50) values of chrysanthemum, mulberry and butterfly pea extracts were 4.24±0.12 mg/ml, 0.59±0.06 mg/ml, and 3.15±0.19 mg/ml, respectively. In addition, the IC(50) values of chrysanthemum, mulberry and butterfly pea extracts against intestinal sucrase were 3.85±0.41 mg/ml, 0.94±0.11 mg/ml, and 4.41±0.15 mg/ml, respectively. Furthermore, the IC(50) values of roselle and butterfly pea extracts against pancreatic α-amylase occurred at concentration of 3.52±0.15 mg/ml and 4.05±0.32 mg/ml, respectively. Combining roselle, chrysanthemum, and butterfly pea extracts with mulberry extract showed additive interaction on intestinal maltase inhibition. The results also demonstrated that the combination of chrysanthemum, mulberry, or bael extracts together with roselle extract produced synergistic inhibition, whereas roselle extract showed additive inhibition when combined with butterfly pea extract against pancreatic α-amylase. CONCLUSIONS: The present study presents data from five plant-based foods evaluating the intestinal α-glucosidase and pancreatic α-amylase inhibitory activities and their additive and synergistic interactions. These results could be useful for developing functional foods by combination of plant-based foods for treatment and prevention of diabetes mellitus.